Rhythms in Plants 2015
DOI: 10.1007/978-3-319-20517-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodism: The Calendar of Plants

Abstract: The daylength varies with the time of the year and can thus be used by plants-and other organisms-to react photoperiodically in developmental steps and morphological features such as cyst formation, germination of zygospores and cell division in certain algae, succulence of stems and leaves, formation of storage organs, and flower induction. The functioning and molecular bases of circadian clocks of plants are mentioned and shown how they are entrained to the day, and whether they are involved in photoperiodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 261 publications
(276 reference statements)
0
1
0
Order By: Relevance
“…This research was evidence of an extraretinal photoreceptor that was found years later in the form of the blue light pigment cryptochrome. This work was only possible because of Wolfgang's excellent skills in developing innovative methods for recording and analyzing all kinds of rhythms, methods that he made available to the scientific community (Engelmann, 2004). For example, he was the first to develop an automatic recording system using infrared light barriers for activity rhythms in flies (Engelmann and Mack, 1978).…”
mentioning
confidence: 99%
“…This research was evidence of an extraretinal photoreceptor that was found years later in the form of the blue light pigment cryptochrome. This work was only possible because of Wolfgang's excellent skills in developing innovative methods for recording and analyzing all kinds of rhythms, methods that he made available to the scientific community (Engelmann, 2004). For example, he was the first to develop an automatic recording system using infrared light barriers for activity rhythms in flies (Engelmann and Mack, 1978).…”
mentioning
confidence: 99%